PERMIAN AND TRIASSIC OF THE RUSHAN-PSHART ZONE (PAMIR) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
Three isolated tectonic blocks Rushan, Pshart and Dunkeldyk have conventionally been grouped into the Rushan-Pshart zone. Because of stratigraphic and structural differences, they should be considered  separately. The present paper mostly deals with the Pshart block, which is subdivided into East and West Pshart. This kind of subdivision may also be applied to the Dunkeldyk  block. A summary of the characteristics of Upper Paleozoic and Mesozoic volcano-sedimentary successions confirms  previous hypotheses, which suggest that these sequences have formed under crustal extension, accompanied  by basaltic volcanism. These earlier models, however, postulated the existence of a vast oceanic area separating the East Pshart from SE Pamir during Late Permian, Triassic, and Jurassic. This ocean closed during the Early Cretaceous. The interpretation preferred in this paper suggests a narrow sea-way, which closed before the Cretaceous.
Keywords: Permian; Triassic; Jurassic; Pamir; Stratigraphy; Paleogeography